Ecological knowledge of regeneration from seed in neotropical forest trees: implications for natural forest management - Guariguata, Manuel R.; Pinard, M.A. (1998)
We discuss the main ecological factors that influence tree recruitment in neotropical moist-and wet forests within the context of timber management based on selective logging. We argue that setting aside protection areas in managed forests as a way to preserve ecological processes may not be sufficient to ensure sustainable levels of tree regeneration, and that a thorough understanding and application of tree seed ecology can help to refine management prescriptions. We review relevant aspects of tree reproductive biology, seed production and dispersal, spatial and temporal constraints on seed availability, disperser implications for biological sustainability in managed forests. Tree seed production can be influenced by the selective removal of neighbors of the same species (due to insufficient pollen transfer). flowering asynchrony, and attributes of the species sexual system. The extent to which an area is supplied by seed can be affected by dispersal mechanism, spatio-temporal limitations to seed dispersal, and tree size-dependent levels of seed production at the species level. Studies of vertebrate-disperser behavior and tree seed deposition in logged forest are scarce and warrant further attention in order to refine our understanding of the dependency of sustained timber production on vertebrate fauna. Although much remains to be learned about tree seed ecology in neotropical logged forests, the baseline information presented here may offer a starting point for developing ecological criteria for seed retention. Furthermore, it may contribute in improving ecologically-based management prescriptions in order to enhance or at least maintain sufficient levels of natural regeneration without the need to rely on artificial regeneration